Continuum modeling of dislocation channels in irradiated metals based on stochastic crystal plasticity. (April 2022) - Liu, Wenbin; Chen, Lirong; Yu, Long; Fu, Jiaqi; Duan, Huiling
Abstract: As a common feature observed in irradiated metallic materials, the formation of dislocation channels has been extensively studied and is considered to play a key role in irradiation embrittlement. However, modeling dislocation channels with the conventional crystal plasticity theory has been a theoretical challenge due to the difficulty of capturing microstructural inhomogeneities. Here a continuum crystal plasticity framework incorporating a stochastic distribution model of critical resolved shear stress (CRSS) is developed to describe the formation of dislocation channels and further plastic flow localization in irradiated materials. We show that the stochastic model is capable of capturing the heterogeneity of microscale plastic strain, which is an inherent feature of metallic materials during plastic deformation. It acts as an important microscale perturbation to trigger the dislocation channel nucleation in irradiated metals, especially for single crystals that lack mesoscale perturbations such as intergranular incompatibility and grain anisotropy. Without predetermining the potential nucleation position of dislocation channels, the stochastic irradiation crystal plasticity framework successfully simulates the dislocation channel formation and plasticity localization in both irradiated single- and polycrystalline copper (Cu), and further indicates the irradiation defect density threshold for the dislocation channel formation. This stochastic model broadens the application of the conventional crystal plasticity framework, and might provide new insights for other studies on plasticity localization, including shear bands formation of metals, mechanical behaviors with heterogeneous deformation and so on. Highlights: We develop a stochastic crystal plasticity model based on inhomogeneous microscale plasticity. The continuum model successfully simulates the dislocation channel formation in irradiated single- and polycrystalline Cu. The distribution profile of plastic strain is 'elongated' with deformation in irradiated materials prior to dislocation channeling The nucleation of the dislocation channel strongly depends on the microscale and mesoscale inhomogeneities.